Realna ocena vrednosti projekta drugi tir železniške povezave Divača-Koper in odgovorno vodenje infrastrukturne investicije - Strah, Bojan (Gradbeni vestnik, 2018)
Professional infrastructure investment management requires that, within each project phase, a revision of costs estimates is made based on the available information and the level of processing of the technical documentation. Estimating the value of an investment on the basis of comparable projects is a process that can serve only as cost orientation in the initial stages of the project. Similarly, value estimates are based on statistically derived market prices for a unit of item of Bill of Quantities, as defined by the project designer. The correct professionally based value-assessment process is to use the ABC (Activity-Based Costing) method and the elaboration of a techno-economic study, which requires detailed knowledge of the project and determining key project activities. The article draws attention to the irregularities in the current cost estimates and procedures of project management and presents the correct procedure for calculating the costs for the construction of the T1 tunnel, which is part of the investment project for the construction of a new railway connection between Divača and Koper. The calculation was made on the basis of the draft investment program and inofficial project documentation for obtaining a construction permit.
Keywords: ABC method; ABC-metoda; bill of quantities; CERP; construction enterprise resource planning; construction manager; cost engineering; cost estimating; drugi tir Divača-Koper; gradnja predorov; načrtovanje virov gradbenega podjetja; ocenjevanje investicij; popis del; project management; projektno vodenje; second track Divača Koper; stroškovni inženiring; tunnel construction; vodja investicije